Binomial Tree Model for Option Pricing: A Theoretical as well as Practical View - Gupta, Devika (2010)
This particular study has been undertaken to implement the Binomial Option Pricing technique using computational software. This has been done with a view to price European as well as American options. Even though most of the option prices are given and available to the users, having a model to price them can prove as a useful tool for analysis and subsequent hedging. The Binomial Tree model has been chosen for valuing American options taking real time market data for stock options that trade on NASDAQ under the Chicago Board Options Exchange. Implied volatility has been used to compute option prices from the program to match their actual market value. This is done with a view to develop a program that has the ability to calculate the price of an option using real time data as close to the actual market price of the option.Volatility is discussed in greater detail and its effect on option prices are observed by varying it in the binomial tree program.